2020
DOI: 10.5539/jsd.v14n1p36
|View full text |Cite
|
Sign up to set email alerts
|

Citrus Farmers Adoption of Sustainable Agriculture Practices and Its Determinants in the Jordan Valley: The Case of Northern Ghor

Abstract: The adoption of sustainable agricultural practices is widely recognized as essential to ensure agricultural sustainability. This study analyzed factors influencing citrus farmers adoption of sustainable agricultural practices (SAPs) in the Northern Ghor of Jordan valley. The study used a quantitative approach. Simple random sampling was adopted to select 115 farmers in the study area. The study found that the largest proportion 44.4% of the citrus farmers had a fairly high adoption rate of SAPs while 13.0% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…The growing design and implementation of AGPTs across developing countries have aroused research interests over the last decades [12]. Nevertheless, the existing literature is overly skewed to analyze the determining factors of AGPTs by crop growers [13][14][15][16]. Meanwhile, the studies on green innovation adoption have highlighted the critical role of attitudinal factors in environmental conservative practices' adoption and implementation [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The growing design and implementation of AGPTs across developing countries have aroused research interests over the last decades [12]. Nevertheless, the existing literature is overly skewed to analyze the determining factors of AGPTs by crop growers [13][14][15][16]. Meanwhile, the studies on green innovation adoption have highlighted the critical role of attitudinal factors in environmental conservative practices' adoption and implementation [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Increased experience with new technologies might be fruitful but repetition of traditional farming knowledge over the rarely improves the sustainability of the farms. Alwedyan and Taani (2020) also found that, probability of adopting multiple SAPs would decrease with increasing farming experience.…”
Section: Determinants Of Adoption Of Sustainable Agriculture Practicesmentioning
confidence: 86%